Mapping review of interventions to reduce the use of restrictive practices in children and young people's institutional settings: The CONTRAST study. (24th May 2022) - Baker, John; Kendal, Sarah; Berzins, Kathryn; Canvin, Krysia; Branthonne‐Foster, Stella; McDougall, Tim; Goldson, Barry; Kellar, Ian; Wright, Judy; Duxbury, Joy
Abstract: Restrictive practices are often used harmfully with children in institutional settings. Interventions to reduce their use do not appear to have been mapped systematically. Using environmental scanning, we conducted a broad‐scope mapping review of English language academic databases, websites and social media, using systematic methods. Included records ( N  = 121) were mostly from the United States and contained details of 82 different interventions. Children's participation was limited. Reporting quality was inconsistent, which undermined claims of effectiveness. Overall, despite a multitude of interventions, evidence is limited. Leaders should consider the evidence, including children's perspectives, before introducing poorly understood interventions into children's settings.